2018
DOI: 10.2105/ajph.2018.304542
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers, Access to Care, and Service Utilization Among Florida Latinos: A Randomized Controlled Trial

Abstract: Among Latinos with poorly controlled diabetes, a 1-year community health worker intervention was associated with improvements in self-reported access to care but not service utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Despite variations in the study settings, methods, and program durations of the identified papers in this review, the findings indicated that Chinese CHWs provided certain types of community-based preventive services on major chronic diseases. These were generally aligned with the results of other international reviews [ 35 , 36 , 37 , 38 ]. However, limited studies in this review focused on NCD risk factors management among general populations, except one sodium reduction program conducted by Li et al [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…Despite variations in the study settings, methods, and program durations of the identified papers in this review, the findings indicated that Chinese CHWs provided certain types of community-based preventive services on major chronic diseases. These were generally aligned with the results of other international reviews [ 35 , 36 , 37 , 38 ]. However, limited studies in this review focused on NCD risk factors management among general populations, except one sodium reduction program conducted by Li et al [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…CHWs are frontline public health workers who are trusted members of or closely familiar with the community they serve. [8][9][10][11] CHWs with appropriate training can serve as effective peer coaches by providing culturally congruent counseling to promote healthy behaviors and motivate patients to engage in proven disease prevention strategies. [12][13][14][15][16][17] CHWs integrated into PC teams can improve care for patients with chronic disease at modest cost, improve preventive care, and address social determinants of health.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the results of this study have the potential to influence current and future policy regarding the need for additional interventions for retention, adherence, and continuity of care to improve treatment adherence and viral load suppression in MDC. If in fact, communities high in Factor 1 (lowest SES, lowest education, and least access to health insurance) are most likely to have high rates of uncontrolled HIV, then we would propose that effective HIV healthcare delivery may need to involve community-based participatory approaches to become more comprehensive with wrap around services from patient navigators to culturally diverse community health workers to medical-legal partnerships, for those of low SES, low education, and low access to health insurance, specifically for Black/African Americans and Hispanic/Latinx in MDC [ 33 36 , 38 , 39 , 41 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve favorable results in HIV control, new interventions that address barriers to improving healthcare access and insurance coverage, as per the health and healthcare determinant of the SDOH, should be implemented. Chronic disease research has shown that interventions utilizing community health workers in underserved populations, particularly racial/ethnic minorities, have had positive effects on health outcomes in terms of prevention and reduced disease progression [33][34][35][36][37]. For both Black/African Americans and Hispanic/Latinx, the use of patient navigators has been shown to be a successful intervention that has had significant effects on improving timely linkage to care, retention in care, and preventing declines in viral suppression [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%